Correlation between Level of Knowledge about Anemia in Pregnant Women and Compliance in Consuming (Fe) Tablets at Sukadana Health Center in 2023 - Fitriani Fitriani; Masluroh Masluroh (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background Pregnancy is the condition of a woman carrying a fetus in the uterus which is the result of sperm cells and ovum cells which will then develop into a baby and will be born at 40 weeks of gestation. Anemia is a condition in which the body has too many red blood cells (erythrocytes). Based on WHO data in 2011, 38.2% of anemia occurs in pregnant women Research objective: To find out the management of the relationship between the level of knowledge about anemia in pregnant women and adherence to consuming tablets (Fe) at the Sukadana Health Center in 2023. Research methodology: The design in this study was to use a quantitative research method with a cross sectional approach. The analysis technique used is the chi square test (X2). Results: analysis using SPSS with a significant level (a = 0.05) obtained results with a p value of 0.014 <0.05 so that ha was accepted which stated that there was a relationship between the level of knowledge of anemia in pregnant women and adherence to consuming FE tablets at the Sukadana Health Center year 2023.